Engineering and economic analysis of the production of sieve shaker for teaching particle size to students with visual impairment - Maryanti, R. (University of Kuwait, 2022)
The purpose of this study was to evaluate the feasibility study in the production of sieve shaker for teaching particle size to students with visual impairment. The sieve shaker is important as a tool for understanding the definition of particles and their sizes, while this equipment has been well developed for engineering purposes. Different from other sieve shakers that are expensive, the present sieve shaker is just for educational goals only (especially for being used in developing countries), making the design of this equipment simpler, user friendlier, and more portable. The feasibility study was done from the engineering and economic perspectives. Engineering analysis was performed based on a simple mass balance analysis, adding it to the calculation of scale-up production from commercially available apparatuses. Economic evaluation was carried out using a number of economic parameters, including gross profit margin, payback period, and net profit value, in which all calculations were done under ideal and nonideal conditions (labor conditions, sales and raw materials, utilities, and external conditions and environmental uncertainties (competition, taxes and subsidiaries)) in 20 years (y) of project. All prices, utilizing components, and specifications for the apparatuses used in the scale-up production were taken based on the available online shopping web. The results of the engineering confirmed that the project was potentially conducted, even in small-scale industries because all processing steps could be carried out using simple equipment that is commercially available in the market. Economic evaluation results showed positive values for all economic parameters with a few exceptions. This research was complemented by some basic theories to support the definition of sieve shaker. Â© 2022 University of Kuwait. All rights reserved.